Ancient and Rare Readings in the Syriac Harklean Version of the Gospel of John and their Significance for its Interpretation - Jutkiewicz, Piotr (The Biblical Annals, 2025)
This paper analyses four intriguing variant readings that are ancient, rare, and unexpectedly transmitted by a relatively late translation of the NT, the Syriac Harklean version. Although the existence of these readings is not a recent discovery, the broader picture emerging from their joint presentation is hoped to encourage a new, less biased perspective from which to approach the Harklean text of the gospels and an enhanced understanding of how the Gospel of John was read and interpreted by its early audiences. This different approach to textual criticism than the traditional quest for one ‘original’ text appreciates even secondary readings exploring their place within larger patterns and is called ‘narrative textual criticism’.